Pemberdayaan Masyarakat melalui Program Babari sebagai Metode Literasi - mimi suhayati; Yusi Maesuri (Universitas Pahlawan Tuanku Tambusai, 2023)
Community empowerment activities through the BABARI program as a creative digital literacy method aimed at the community from the elementary, middle, and high school education levels are carried out once a week, and the results of reading and reviewing their writings will be published on the website. The method used is Participatory Rural Appraisal (PRA). This activity aims to help people to love reading and not be left behind by advanced technology. For this reason, BABARI was programmed as a form of digital literacy assistance to the community in Kampung Warung Jogjog. This activity received a positive response from the community because it became a need for young people to add insight into knowledge and skills in the field of reading and writing. In addition, it is hoped that this program will continue to grow and that donors from the Education Office, Library, and Archives Service are needed to add books and technological equipment as additional support for their digital literacy activities.